Diabetes mellitus not an unfavorable factor on the prognosis of hepatitis C virus‐related hepatocellular carcinoma. Issue 1 (1st April 2017) - Yoshida, Naoki; Midorikawa, Yutaka; Higaki, Tokio; Nakayama, Hisashi; Tsuji, Shingo; Matsuoka, Shunichi; Ishihara, Hisamitsu; Moriyama, Mitsuhiko; Takayama, Tadatoshi
Abstract : Aim: Diabetes mellitus (DM) is a potential risk factor for hepatocarcinogenesis, especially in patients with hepatitis C virus (HCV) infection. We aimed to elucidate whether DM influences the surgical outcomes of patients with hepatocellular carcinoma (HCC). Methods: Our patients were routinely controlled to keep urinary glucose excretion to less than 3.0 g/day before surgery, and the serum glucose level under 200 mg/dL after surgery. The surgical outcomes and postoperative complications of 112 patients with HCV‐related HCC with DM (DM group) were compared to those of 112 propensity‐matched patients without DM (non‐DM group). Results: After a median follow‐up of 3.2 years (range, 0.2–11.3 years), the median overall (5.2 years; 95% confidence interval, 3.8–6.5 years) and recurrence‐free survival (2.2 years; 1.7–2.9 years) in the DM group were not significantly different from those (6.3 years; 5.4–7.1 years, P = 0.337; and 2.2 years; 1.7–3.6 years, P = 0.613) in the non‐DM group. The independent factors related to overall survival were the background liver (hazard ratio, 2.06; 95% confidence interval, 1.27–3.39, P = 0.014) and tumor differentiation grade (2.07; 1.14–4.05, P = 0.015). Thirty‐two patients (28.5%) in the DM group and 32 patients (28.5%) in the non‐DM group had morbidities after operation, with no significant difference between the groups ( P = 1.000). Furthermore, postoperative control status of DM did not affect the prognostic outcome. Conclusion: Diabetes mellitus does not affect the surgical outcomes of patients with HCV‐related HCC, and it is not an unfavorable factor when selecting candidates for liver resection of HCC.